The Nitric Oxide Synthase Inhibitor NG-Nitro-L-Arginine Methyl Ester Diminishes the Immunomodulatory Effects of Parental Arginine in Rats with Subacute Peritonitis. - Hui-Chen Lo; Ching-Yi Hung; Fu-Huan Huang; Tzu-Cheng Su; Chien-Hsing Lee (PLoS ONE, 2016)
The combined treatment of parenteral arginine and the nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME) have been shown to improve liver function and systemic inflammation in subacute peritonitic rats. Here, we investigated the effects of single and combined parenteral arginine and L-NAME treatments on leukocyte and splenocyte immunity. Male Wistar rats were subjected to cecal punctures and were intravenously given total parenteral nutrition solutions with or without arginine and/or L-NAME supplementations for 7 days. Non-surgical and sham-operated rats with no cecal puncture were given a chow diet and parenteral nutrition, respectively. Parenteral feeding elevated the white blood cell numbers and subacute peritonitis augmented the parenteral nutrition-induced alterations in the loss of body weight gain, splenomegaly, and splenocyte decreases. Parenteral arginine significantly increased the B-leukocyte level, decreased the natural killer T (NKT)-leukocyte and splenocyte levels, alleviated the loss in body weight gain and total and cytotoxic T-splenocyte levels, and attenuated the increases in plasma nitrate/nitrite and interferon-gamma production by T-splenocytes. L-NAME infusion significantly decreased NKT-leukocyte level, tumor-necrosis factor (TNF)-alpha production by T-splenocytes and macrophages, and interferon-gamma production by T-leukocytes, monocytes, and T-splenocytes, as well as increased interleukin-6 production by T-leukocytes and monocytes and nitrate/nitrite production by T-leukocytes. Combined treatment significantly decreased plasma nitrate/nitrite, the NKT-leukocyte level, and TNF-alpha production by T-splenocytes. Parenteral arginine may attenuate immune impairment and L-NAME infusion may augment leukocyte proinflammatory response, eliminate splenocyte proinflammatory and T-helper 1 responses, and diminish arginine-induced immunomodulation in combined treatment in subacute peritonitic rats.